2020
DOI: 10.1101/2020.06.19.159970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Inactivation of SARS-CoV-2 by Silicon Nitride, Copper, and Aluminum Nitride

Abstract: IntroductionViral disease spread by contaminated commonly touched surfaces is a global concern. Silicon nitride, an industrial ceramic that is also used as an implant in spine surgery, has known antibacterial activity. The mechanism of antibacterial action relates to the hydrolytic release of surface disinfectants. It is hypothesized that silicon nitride can also inactivate the coronavirus SARS-CoV-2.Methods SARS-CoV-2 virions were exposed to 15 wt.% aqueous suspensions of silicon nitride, aluminum nitride, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(64 reference statements)
2
16
0
Order By: Relevance
“…The remarkable finding in the present study is that a one-minute exposure to a 5% solution of Si3N4 resulted in 85% inactivation of SARS-CoV-2, while Vero cell viability was minimally impacted even after a 48 hour exposure to a 20% concentration of the same material. This finding is consistent with previous work showing that Si3N4 exerts a fortuitous dual effect, whereby the material can inactivate viruses 12,26 and inhibit bacterial biofilm formation 29 without negatively impacting mammalian cell viability. The present study is also consistent with a recent investigation that showed the rapid inactivation of SARS-CoV-2 upon exposure to 15% (w/v) Si3N4, 12 and related data showing that the antiviral effect of Si3N4 may be generally applicable to other single-strand RNA viruses such as Influenza A, Feline calicivirus, and Enterovirus.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The remarkable finding in the present study is that a one-minute exposure to a 5% solution of Si3N4 resulted in 85% inactivation of SARS-CoV-2, while Vero cell viability was minimally impacted even after a 48 hour exposure to a 20% concentration of the same material. This finding is consistent with previous work showing that Si3N4 exerts a fortuitous dual effect, whereby the material can inactivate viruses 12,26 and inhibit bacterial biofilm formation 29 without negatively impacting mammalian cell viability. The present study is also consistent with a recent investigation that showed the rapid inactivation of SARS-CoV-2 upon exposure to 15% (w/v) Si3N4, 12 and related data showing that the antiviral effect of Si3N4 may be generally applicable to other single-strand RNA viruses such as Influenza A, Feline calicivirus, and Enterovirus.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous work showing that Si3N4 exerts a fortuitous dual effect, whereby the material can inactivate viruses 12,26 and inhibit bacterial biofilm formation 29 without negatively impacting mammalian cell viability. The present study is also consistent with a recent investigation that showed the rapid inactivation of SARS-CoV-2 upon exposure to 15% (w/v) Si3N4, 12 and related data showing that the antiviral effect of Si3N4 may be generally applicable to other single-strand RNA viruses such as Influenza A, Feline calicivirus, and Enterovirus. 26 Taken together, these studies suggest that Si3N4 may be a suitable material platform for the development of fabrics for personal protective equipment such as masks, and also to manufacture commonly-touched surfaces where viral persistence may encourage the spread of disease.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations